Priming effect of ascorbic acid on the growth and biomass of quinoa under saline conditions - Shah, Sulaiman; Khan, Yaseen; Cheng, Zijun; Bouskout, Mohammed; Zhang, Tao; Yan, Hong; Wang, Mingming (Frontiers in Plant Science, 2025)
Ascorbic acid (ASA) is often recommended to mitigate the effects of saline stress on crop growth. However, no such research exists on its priming effect on the growth of quinoa (Chenopodium quinoa Willd.). Thus, the main goal of this study was to evaluate the potential benefits of ASA (0.1 and 0.5 μM) against salt-induced stress in quinoa seedlings. The results showed that ASA significantly improved germination, and biomass, especially fresh weight (≥47.14%) and dry weight (≥83.33%) even higher than CK, indicating enhanced plant vigor under such salt stress of 200 mM. Additionally, ASA-treated plants enhanced chlorophyll and carotenoid biosynthesis, with low ASA increased carotenoids by 95.45%, improving photosynthesis. Furthermore, ASA enhanced gas exchange, non-photochemical quenching (NPQ), and antioxidants enzyme activities, suggesting improvement in energy dissipation and potential support for oxidative stress tolerance. Notably, metabolic indicators, especially proline (≥29.89%) showed higher levels, indicating enhanced osmotic adjustment. Moreover, ASA effectively mitigated sodium (Na+) and chloride (Cl−) in roots through potassium (K+) uptake by at least 93.41% and elevated K+ levels by 99.76% in shoots, underscoring its role in mediating ion homeostasis under salinity. This study provides the first evidence that ASA could enhance biological, physiological and biochemical responses in quinoa. Applying ASA at 0.1 μM/L is feasible and effective as a priming concentration under suitable salt stress conditions.